Digestibilidade aparente de dietas contendo feno de Tifton 85 (Cynodon spp) e níveis crescentes de feijão (Phaseolus vulgaris) moído ou expandido, em ovinos - Igor Ribeiro da Glória (2007)
Twenty male sheep were submitted to a randomized experimental design that evaluated increasing levels (12, 24, 36 e 47%) of a concentrate (90% kidney bean ground or expanded and 10% ground corn), to a diet of Tifton 85’s hay (Cynodon spp). Apparent digestibilities and intakes of DM, CP, NDF, ADF, hemicellulose, cellulose and crude energy were determined. Energy and nitrogen balance were also studied. There were no differences in DM intake as it was controlled for maintenance needs, but there where linear increases in the consumptions of CP, digestible and metabolizable energy. The increasing levels of concentrate in the diets caused linear increase of DM, CP and crude energy digestibilities, but did not alter NDF and hemicellulose digestibilities. ADF and cellulose digestibilities showed quadratic responses. Nitrogen balances were positive for all diets. Nitrogen retentions were superior for diets with expanded kidney bean. Expansion did not alter digestible and metabolizable energies, and mean values were 3,68 Mcal DE/Kg DM and 3,15 Mcal ME/Kg DM of ground and expanded kidney beans.